Contamination acts as a genotype-dependent barrier to gene flow, causing genetic erosion and fine-grained population subdivision in Mussels from the Strait of Istanbul - Theodorakis, Christopher W (Ecotoxicology (London, England), 2024)
© 2023. The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.